High-intensity Interval Versus Moderate-intensity Continuous Heated Water-based Exercise On Cardiovascular Variables In Hypertensive Older Individuals - Marcal, Isabela R. [UNESP] (2020)
Sao Paulo State Univ UNESP, Bauru, SP, Brazil